Effect of dietary supplementation of formic acid, butyric acid or their combination on carcass and meat characteristics of broiler chickens - Sugiharto, S.; Yudiarti, T.; Isroli, I.; Widiastuti, E.; Wahyuni, H. I.; Sartono, T. A.; Nurwantoro, N.; Al-Baarri, A. N. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The objective of the present study was to evaluate the impact of dietary supplementation of formic acid, butyric acid or their combination on carcass and meat characteristics of broiler chicks. A number of 288 day-old-chicks (Lohmann MB-202 meat broilers) were distributed to four groups, including CONT (basal diet with no additive as a control), FORM (basal diet containing 0.1% formic acid), BUTR (basal diet with 0.03% butyric acid) and FORM+BUTR (basal diet with 0.1% formic and 0.03% butyric acid). At day 35 the birds were slaughtered and eviscerated, and from which the breast meat was obtained. Carcass and cut yields of broilers were not different (P>0.05) among CONT, FORM and BUTR birds. The combination of formic and butyric acids increased (P<0.05) the relative weight of back of broilers. Meat pH value was higher (P<0.05) in organic acids treated than in non-treated birds. Organic acids lowered (P<0.05) drip loss of broiler meat. Butyric acid increased (P<0.05) moisture and decreased (P<0.05) the content of meat protein. Formic acid increased (P<0.05), whereas butyric acid and combination of formic and butyric acids decreased (P<0.05) lightness values of breast meat. Yellowness values of meat increased (P<0.05) with organic acid administration. Intense bands of 25 kDa (phosphoglycerate mutase) was observed in most of meat samples from the treated birds, but not in meat from the control birds. In conclusion, dietary supplementation of organic acids was capable of improving the meat quality of broiler meats. The treatments may prevent the pale, soft and exudative (PSE)-like condition in broiler meats.